Effects of resistance exercise training on oxygen consumption and minute by minute efficiency during the six-minute walk test in female breast cancer survivors - Muñoz-Cofre, Rodrigo; Artigas-Arias, Macarena; Valenzuela-Aedo, Fernando; Escobar-Cabello, Máximo; Sol, Mariano del; Conei, Daniel; Sapunar, Jorge; Curi, Rui; Marzuca-Nassr, Gabriel Nasri (Frontiers in Physiology, 2025)
ObjectiveTo determine the effects of resistance exercise training (RET) on oxygen consumption and minute-by-minute efficiency during the Six-Minute Walk Test (6MWT) in healthy postmenopausal female breast cancer survivors.MethodsEleven healthy postmenopausal women, all breast cancer survivors, participated in a 12-week progressive RET program consisting of 36 training sessions. Sessions were conducted three times per week on nonconsecutive days and focused on both upper and lower limbs. Training loads ranged from 60% to 80% of participants’ one-repetition maximum (1RM). Before and after the 12-week program, participants underwent the 6MWT using a PNOE® metabolic analyzer. In addition to walking distance, oxygen consumption (VO2) and carbon dioxide output (VCO2) were assessed as key variables.ResultsFollowing the intervention, the distance covered in the 6MWT significantly increased from 572.9 ± 62.6 m to 604.7 ± 39.9 m (p < 0.001). Work performed during the 6MWT (6MWORK) also increased significantly from 38415 ± 5611 to 40883 ± 5262 (p = 0.001). No significant differences were observed in relative VO2 (p = 0.116) or absolute VCO2 (p = 0.111). However, minute-by-minute VO2 analysis revealed a significant decrease in oxygen consumption during minutes 4, 5, and 6 of the 6MWT (28.91 ± 5.85 to 25.88 ± 5.61, p = 0.030; 32.08 ± 6.32 to 28.37 ± 5.40, p = 0.032; and 32.46 ± 6.57 to 28.60 ± 5.61, p = 0.045, respectively).ConclusionFollowing the RET program as a single-arm pre- and post-intervention, a significant decrease in submaximal VO2 was observed during the second half of the 6MWT, specifically between minutes 4 and 6, accompanied by an increase in submaximal VCO2, which may have contributed to the significant improvements in 6MWT and 6MWORK distance.